The talk - Bell, Darrin (Henry Hold and Company, 2024)
"Darrin Bell was six years old when his mother told him he couldn’t have a realistic water gun. She said she feared for his safety, that police tend to think of little Black boys as older and less innocent than they really are.Through evocative illustrations and sharp humor, Bell examines how The Talk shaped intimate and public moments from childhood to adulthood. While coming of age in Los Angeles―and finding a voice through cartooning―Bell becomes painfully aware of being regarded as dangerous by white teachers, neighbors, and police officers and thus of his mortality. Drawing attention to the brutal murders of African Americans and showcasing revealing insights and cartoons along the way, he brings us up to the moment of reckoning when people took to the streets protesting the murders of George Floyd and Breonna Taylor. And now Bell must decide whether he and his own six-year-old son are ready to have The Talk."